MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE DAN PENGARUHNYA TERHADAP PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK - Suci Indrayani (Jurnal Edukasi dan Penelitian Matematika, 2018)
Understanding of mathematical concepts is one of basic ability that must be developed in learning mathematics. However, from students’ learning result, it is seen that students’ understanding of mathematical concepts in eight grade at SMP Negeri 15 Padang is still low. It is caused students who are less active in the learning process. In addition, students are still not able in resolving questions that are different from the examples. Solution to overcome the problem is cooperative learning model think talk write type. This research aims to know whether students’ understanding of mathematical concepts using cooperative learning model think talk write type is better than using conventional learning. Type of this research is quasi experiment and uses static group design. The sample of this research were class VIII.4 and VIII.5. Instrument used in this research was test in essay form. Results of research show that understanding of mathematical concepts of students using cooperative learning model think talk write type is better than using conventional learning.Keywords– conventional learning, cooperative learning, think talk write, understanding of mathematical concepts